Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

give me answer

Asked by 15th March 2010, 7:26 PM
Answered by Expert
Answer:

Sn = n(2a0+(n-1)d)/2

Sq = q(2a0+(q-1)d)/2 = 2q+3q2     ..............(0)

2a0+(q-1)d = 4+6q      .... (1)

Put q = q+1 in (0),

Sq+1 = (q+1)(2a0+qd)/2 = 2(q+1)+3(q+1)2     ..............(0)

2a0+qd = 4+6(q+1)    ... (2)

Subtracting (2) from (1),

d = 6.

The common difference is, 6.

Regards,

Team,

TopperLearning.

Answered by Expert 15th March 2010, 7:43 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!